Nymphaea vanildae (Nymphaeaceae): A new species from the Caatinga in Brazil - de Lima, Carla Teixeira; Guilietti, Ana Maria (Phytotaxa, 2013)
Nymphaea vanildae (Nymphaeaceae) is described and illustrated as a new species from the Caatinga region in Brazil, and placed in Nymphaea subg. Hydrocallis. This species is characterized by having nocturnal flowers, elliptic and delicate leaves, a clear distinction between the perianth and androecium, linear carpellary appendages and four or more series of proliferate pseudanthia, which distinguishes it from all species in the genus.